Analytical QBD Approach to Redefine the Quality of Pharmaceuticals: A Review - Shaik Ayesha Ameen; Nagaraju Pappula (Journal of Pharmaceutical Research)
As per the present scenario traditional techniques of quality by testing of finished pharmaceutical products have proved to be unsatisfactory, although focus on 'Total quality assurance can be attained only by in-process testing and analysis. The Quality by Design (QbD) idea has already been established and applied in all nations that adhere to the International Conference on Harmonization Guidelines. The proposed ICH Guidelines Q8 for pharmaceutical development, Q9 for quality risk management, and Q10 for pharmaceutical quality systems offer a foundation for incorporating quality into the product. Other components are being added and integrated into the analytical method development process, including as Quality Risk Management, the Pharmaceutical Quality System, and Process Analytical Technology (PAT) guidelines. The Quality by Design (QbD) idea has already been established and applied in all nations that adhere to the International Conference on Harmonization Guidelines. The proposed ICH Guidelines Q8 for pharmaceutical development, Q9 for quality risk management, and Q10 for pharmaceutical quality systems offer a foundation for incorporating quality into the product. Other components are being added and integrated into the analytical method development process, including as Quality Risk Management, the Pharmaceutical Quality System, and Process Analytical Technology (PAT) guidelines. They are widely acknowledged in the business as AQbD (Analytical Quality by Design) ideas. This paper attempts to summarize QbD achievements to date, regulatory perspectives on QbD, a comparative examination of conventional and analytical QbD techniques in method development, and issues about its fundamental application. Keywords Quality by Design, Design of Experiments, Analytical Quality, Critical Quality Attributes Analytical Target Profile, Process Control